2008
DOI: 10.1248/jhs.54.216
|View full text |Cite
|
Sign up to set email alerts
|

Mevalonate Pyrophosphate Decarboxylase is Predominantly Located in the Cytosol of both B16 and B16F10 Cells in Mouse Melanoma Treated with Lovastatin

Abstract: Recently, it has been questioned whether mevalonate pyrophosphate decarboxylase (MPD) is predominantly located in the peroxisomes or cytosol. We previously reported that a small amount of MPD in the liver of rats fed a CP diet (5% cholestyramine and 0.1% pravastatin) existed in the peroxisomes, although MPD is predominantly located in the cytosol in the liver of rats fed normal chow and a CP diet for 12 days. In the present study, we examined the subcellular distribution of MPD in mouse melanoma cells (B16 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…However, Hogenboom et al (2004) showed that both endogenous human MVD and overexpressed MVD were localized in cytosol. Consistent with this result (Michihara et al, 2008) also showed that MVD is predominantly located in the cytosol of both B16 and B16F10 cells in mouse. Unlike animals, MVD has been reported to be localized in peroxisomes in plants (Clastre et al, 2011; Simkin et al, 2011).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, Hogenboom et al (2004) showed that both endogenous human MVD and overexpressed MVD were localized in cytosol. Consistent with this result (Michihara et al, 2008) also showed that MVD is predominantly located in the cytosol of both B16 and B16F10 cells in mouse. Unlike animals, MVD has been reported to be localized in peroxisomes in plants (Clastre et al, 2011; Simkin et al, 2011).…”
Section: Introductionsupporting
confidence: 81%
“…Mevalonate diphosphate decarboxylase has been reported to localize in cytosol or peroxisomes in plants or animals (Kovacs et al, 2002; Hogenboom et al, 2004; Michihara et al, 2008; Clastre et al, 2011; Simkin et al, 2011). However, studies on the subcellular localization of Erg19 homologs in filamentous fungi are limited.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight of MPD (43 kDa) in HepG2 cells was similar to that in humans reported by Toth et al 22) There is known to be a marked increase in the enzyme involved in cholesterol biosynthesis after treatment with LDS containing lovastatin, an HMGCoA reductase inhibitor. 14,21,23) To further establish whether the 43-kDa protein was MPD, immunoblot analysis of HepG2 and Cos7 cells treated with lovastatin was performed. When immunoblot analysis was carried out using a crude extract of HepG2 cells treated with various concentrations of lovastatin for 120 hr (medium was changed two times), the level of the 43-kDa protein was markedly higher (10-fold by 1 µM, 18-fold by 5 µM, and 20-fold by 10 µM lovastatin) than that of cells without lovastatin (Fig.…”
Section: Identification Of Mpd In Hepg2 and Cos7 Cellsmentioning
confidence: 99%
“…We previously reported that MPD was predominantly present in the cytosol of rat hepatocytes, 12) normal rat kidney (NRK) cells, 12) or mouse melanoma (B16F10 and B16) cells 13,14) treated with FBS, since MPD was mainly present in the medium (cytosolic fraction) in these cell types permeabilized with digitonin. Hogenboom et al reported that both endogenous MPD in human fibroblasts, human liver, CV-1, and HEK293 (human kidney) cells, and overexpressed human MPD in human fibroblasts, HEK293, and CV-1 cells treated with LDS, were present in the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little information on the gene expression of MPD in rats, although analyses of the MPD protein have been performed. [6][7][8][9][10][11][12][13] Thus, we examined the distribution of the mRNA levels in Wistar rat tissues by real-time PCR, to clarify the relationship between protein and mRNA levels of MPD. Next, we compared the mRNA levels of MPD in liver and brain between SHRSP and normotensive WKY.…”
Section: Introductionmentioning
confidence: 99%